Revisiting Women Empowerment Through a Cultural Lens a In-Depth Analysis of Empowerment Methodologies in Horticulture in Rural Ethiopia - De Smet, Sarah; Boroş, Smaranda (Frontiers in Psychology, 2021)
As previous research in international development has clearly demonstrated (see Banerjee & Prasad, 2008 for an overview), cultural values have an impact on the conceptualization of empowerment. In this paper we explore the implications of Power Distance as a cultural dimension for the use of participatory methodologies towards achieving women empowerment in emerging economies. Our critical analysis of cultural differences between the intervention provider (a Western-based NGO ) and the community (rural, Ethiopian) reveals how discrepancies in the perception of cultural values impacted the different stages of the intervention. These discrepancies ranged from the principles of facilitation (facilitation from the back and its paradoxical effects in such hierarchical contexts) to the focus on tools (on equality between individuals rather than focus on the family as the smallest unit); from the selection criteria of participants (highly vulnerable groups; one spouse per family; number of participants from one community – all of which prevented more powerful impact of the intervention in the long run) to how they are organized during trainings (the ratio of mixed vs segregated groups and the criteria of group segregation – this can play a large role in regard to the potential openness of conversations and the creation of safe spaces to explore new identities which are the key to empowerment). Through all the stages of the intervention, we make suggestions on how to better implement such methodologies in the future, in a context-sensitive manner, by taking into account the cultural differences in assumptions and practices.